Developing Online Learning Oriented Learning Devices to Improve Mathematic Abstraction and Self-Efficacy Abilities Istiqlal Delitua Junior High School VII Class Student - Elidar Tanjung; Izwita Dewi; Mulyono Mulyono (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This research is a development research conducted at SMP Istiqlal Delitua which aims to find out how; 1) the level of validity, effectiveness and practicality of learning tools developed in improving students' mathematical abstraction abilities and self-efficacy; 2) Increasing students' mathematical abstraction abilities and self-efficacy in implementing online learning-oriented learning tools. This study produces an online learning-oriented learning tool which is carried out in accordance with the Dick & Carey development model procedure. The results of this study are the learning tools developed; 1) valid, both content and construct validity, 2) practical, seen from the validator's assessment and teacher's observation in managing learning, 3) effective, seen from the completeness of learning, student responses and learning time; 4) improvement of students' mathematical abstraction ability; 5) increased student self-efficacy in the high category.